POTENSI BEBERAPA JENIS TEPUNG RUMPUT LAUT UNTUK MENINGKATKAN KADAR HDL (HIGH DENSITY LIPOPROTEIN) PLASMA TIKUS WISTAR HIPERKOLESTEROLEMIA - Julyasih, K. Sri Marhaeni (UPN VETERAN JAWA TIMUR, 2011)
Several types of seaweed in Bali has been generally consumed by local people as vegetable, such as Caulerpa spp. (local name Bulung Boni), Gracillaria spp (local name Bulung Sangu) and Euchema spinosum, but has not been reported its potential effect to increase high density Lipoprotein (HDL) levels. Therefore it is necessary to determine of plasma HDL cholesterol level of Wistar rat after treated Caulerpa spp, Gracillaria spp. and Euchema spinosum. This experimental study used completely randomized design. Research using a total of 32 Wistar rats divided into eight sample groups of equal size, all fed with a diet high in cholesterol content. The eight sample groups were respectively designated as negative control group, positive control group, and six treated sample groups, respectively fed orally with a dose of 1 g and 1,5 g seaweed flour of Caulepa spp. 1g and 1,5 g of Gracilaria spp., and 1 g and 1,5 g Euchema spinosum per 100g body weight per day. Each treatment was repeated four times. Our study showed that rat fed with high cholesterol diet and treated Caulerpa spp., Gracilaria spp., and E.spinosum with a dose of 1 g and 1.5 g/100 g body weight rat / day were associated with statistically significantly increased plasma HDL level (p <0.05) as compared with those of rats fed with high-cholesterol diet without treated Caulerpa spp., Gracilaria spp., and E.spinosum. The studied concuded that plasma HDL level of Wistar hypercholesterolemia fed Caulerpa spp., Gracilaria spp., and E.spinosum flour with dose of 1 g or 1,5 g higher than Wistar rat without treated seaweeds flour. Rats fed E.spinosum with dose of 1.5 g , the plasma HDL level highest than the other treatment.Keywords : Caulerpa spp., Gracilaria spp., E.spinosum, HDL, hypercholesterolemic